DAMPAK COVID-19 TERHADAP TREN HARGA SAHAM PADA SEKTOR HEALTCARE DI INDONESIA - Rezky Amanda, Tiara; Ahmar, Nurmala (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2019)
This study aims to see the impact of Covid-19 on stock price trends in the healthcaresector in Indonesia. This study uses an event study, which means the data used in thisstudy are financial market data to measure the impact of an event on company valuesuch as share prices of healthcare companies. on companies that have been listed onthe Index in the period July 2020 to June 2021 in a row. In common, there was apositive correction at the end of 2020 from August to December 2020. Meanwhile, in2021 at the beginning of the year, stock prices began to decline from January to April,in line with the condition of the impact of the pandemic experienced by Indonesia inthe second year. Until March to June 2021, the closing price at the end of the monthbegan to see a movement towards a positive correction, it is predicted that the nextmonth towards the end of the year will be the right time to invest, stock prices towardsthe end of the year will experience an increase in prices.